2019
DOI: 10.7717/peerj.6441
|View full text |Cite
|
Sign up to set email alerts
|

Potential antidiabetic effect of ethanolic and aqueous-ethanolic extracts ofRicinus communisleaves on streptozotocin-induced diabetes in rats

Abstract: Recently, herbal drugs and their bioactive compounds have gained popularity in the management of diabetes mellitus (DM), which has become an epidemic disease all over the world and is especially prevalent in the Kingdom of Saudi Arabia (KSA). This study aimed to investigate the antidiabetic effect of ethanolic and aqueous-ethanolic extracts of wild Ricinus communis (R. communis) leaves in streptozotocin (STZ) induced diabetic rats. Diabetic rats were administered orally with the mentioned extracts at doses of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 28 publications
5
27
0
Order By: Relevance
“…In the present study, turmeric showed improvement in liver enzymes in the low‐dose group, while the high‐dose and oral curcumin treatment caused an elevation of liver enzymes, especially the ALT serum levels, which is an indication of a dose‐dependent effect of curcumin. Liver enzyme levels are an indicator of the liver cell integrity, and an increase is mostly associated with liver cell damage (Gad‐Elkareem, Abdelgadir, Badawy, & Kadri, , p.; Swamy, Nagalakshmi, Santhosh, & Yogesh, ); therefore, higher doses of turmeric and curcumin as an oral supplement should be avoided in future studies and in clinical trials since they are potentially hepatotoxic.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, turmeric showed improvement in liver enzymes in the low‐dose group, while the high‐dose and oral curcumin treatment caused an elevation of liver enzymes, especially the ALT serum levels, which is an indication of a dose‐dependent effect of curcumin. Liver enzyme levels are an indicator of the liver cell integrity, and an increase is mostly associated with liver cell damage (Gad‐Elkareem, Abdelgadir, Badawy, & Kadri, , p.; Swamy, Nagalakshmi, Santhosh, & Yogesh, ); therefore, higher doses of turmeric and curcumin as an oral supplement should be avoided in future studies and in clinical trials since they are potentially hepatotoxic.…”
Section: Discussionmentioning
confidence: 99%
“…The non-diabetic rats (negative control) also received normal saline. After 72 h STZ administration, tail blood samples of the overnight fasted rats were collected to measure blood glucose levels [28].…”
Section: Induction Of Diabetesmentioning
confidence: 99%
“…Non-diabetic animals received (60 mg/kg) thymol and thymol nano polymer by gastric gavage needle (NG tube). The untreated normal and diabetic rats were given normal saline [28].…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…exBenth, T. polium L., T. popovii R.A. King, and T. yemense Defl [6]. Most plant extracts and their bioactive molecules have been shown to be scavengers of free radicals, which form the basis of their therapeutic potential [7][8][9][10][11]. Their antioxidant nature has been closely linked with the cancer-preventing property of a plant-derived compound due to the fact that the inhibition of oxidative stress reduces mutations and chromosomal aberrations, which initiate carcinogenesis [12].…”
Section: Introductionmentioning
confidence: 99%